Perceptions and Portrayals of Skin Cancer among Cultural Subgroups. (28th January 2014) - Kelly, Stephanie; Miller, Laura E.; Ahn, Ho-Young; Haley, J. Eric
Abstract : Health communication scholars have a responsibility to be certain that both healthcare practitioners and government agencies accurately communicate health information to the public. In order to carry out this duty, health communication scholars must assess how messages are being received and if they are being received at all by the public. This paper details a two part study which assesses this phenomenon within the context of skin cancer. Study 1 utilized 29 in depth qualitative interviews to identify subcultures among college students whose communication puts them at risk for skin cancer by encouraging poor sun exposure behaviors. The results indicate that farmers, African Americans, and individuals who regularly participate in outdoor athletics are at risk groups. Study 2 reports a content analysis of the known population of skin cancer Public Service Announcements (PSAs) available via the internet in 2013. The aforementioned groups were not present in any of the PSAs. Detailed results and implications are discussed.